2016
DOI: 10.4049/jimmunol.1501084
|View full text |Cite
|
Sign up to set email alerts
|

CysLT1 Receptor Is Protective against Oxidative Stress in a Model of Irritant-Induced Asthma

Abstract: The bronchoconstrictive and proinflammatory properties of cysteinyl leukotrienes (cysLTs) in allergic asthma mediate their effects predominantly through the cysLT1 receptor (cysLT1R). However, the role of cysLTs and cysLT1R in innate immune-triggered asthma is largely unexplored. We explored the synthesis of cysLTs and cysLT1R as determinants of airway responses in an oxidative stress–induced model of irritant asthma. Wild-type (WT) mice exposed to 100 ppm Cl2 for 5 min had airway neutrophilia, increased cysLT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 59 publications
(56 reference statements)
1
9
0
1
Order By: Relevance
“…In turn, oxidative stress triggers Nrf2 translocation and the induction of second‐phase enzymes that may limit the effects of oxidative damage. Consistent with previous published results (McGovern et al, ), Chlorine caused translocation of Nrf2 to the nucleus in the airway epithelium. Although we found evidence of enhancement of this translocation in bronchial epithelial cells in vivo by montelukast treatment, mRNA expression of Nrf2‐dependent enzymes in the lung parenchyma was not significantly further up‐regulated by montelukast.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In turn, oxidative stress triggers Nrf2 translocation and the induction of second‐phase enzymes that may limit the effects of oxidative damage. Consistent with previous published results (McGovern et al, ), Chlorine caused translocation of Nrf2 to the nucleus in the airway epithelium. Although we found evidence of enhancement of this translocation in bronchial epithelial cells in vivo by montelukast treatment, mRNA expression of Nrf2‐dependent enzymes in the lung parenchyma was not significantly further up‐regulated by montelukast.…”
Section: Discussionsupporting
confidence: 93%
“…Montelukast inhibited the development of AHR after chlorine exposure implicating CysLTs in its development. We have demonstrated that these mediators are synthesized following chlorine exposure with a slow time course, reaching a peak by 24 h after exposure (McGovern et al, ). Hypochlorite activates TRPA1 channels which leads to neuropeptide release from airway sensory nerves (Hox et al, ), which in the context of hyperpnea‐induced bronchoconstriction is upstream of CysLT release (Yang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Variation in the CYSLTR1 gene modulates asthma risk as well as adenoid hypertrophy progression, and it has been implicated in the disease outcome of colorectal, prostate, and squamous cell carcinoma [17][18][19][20][21]. Moreover, CYSLTR1 is highly expressed in the normal human skin epidermis, but its expression was found to be even higher in atopic dermatitis [22].…”
Section: Discussionmentioning
confidence: 99%
“…42 Although studies examining the role of cysLTs in EpC function are sparse, CysLT 1 R signaling conferred protection from epithelial damage in a model of airway injury induced by (Cl 2 )-elicited oxidative stress. 43 CysLT 3 R/GPR99 is expressed dominantly by murine respiratory EpCs. Intranasal administration of LTE 4 to wild-type (WT) mice elicited mucin release by goblet cells, which was abrogated in CysLT 3 R-null mice.…”
Section: Effects On Epcsmentioning
confidence: 99%